Modular Reference Architecture for Secure Financial Cloud Systems: Components and Integration Framework - Naga Chand Putta (International Journal of Computational and Experimental Science and Engineering, 2025)
This article proposes a comprehensive reference architecture designed specifically for financial enterprise systems transitioning to cloud environments. The framework addresses the unique challenges faced by financial institutions during cloud migration, including regulatory compliance, security concerns, and integration complexity with legacy systems. Drawing on implementation data from numerous financial organizations, the architecture encompasses five critical domains: core business functionality, data management, security and compliance, integration capabilities, and operational excellence. Key components include a robust data ingestion layer, domain-driven microservices, sophisticated workflow orchestration, polyglot persistence strategies, and legacy system integration patterns. The architecture incorporates security-by-design principles with comprehensive regulatory alignment across frameworks such as SOC 2, GDPR, and SOX, while supporting hybrid and multi-cloud deployment models. Through detailed case studies spanning retail banking, capital markets, and insurance sectors, the framework demonstrates significant improvements in implementation timelines, operational efficiency, security posture, and cost optimization. The article concludes with emerging trends, research gaps, and adoption recommendations to guide financial institutions through successful cloud transformation.